Clinical Risk Factors of Thrombosis in Children after Congenial Heart Diseases Management - Vasily A. Lastovka; Rustem F. Tepaev; Olga B. Gordeeva; Anuar R. Bidzhiev; Elena A. Fedyaeva (Union of pediatricians of Russia, 2020)
Background. Development of thrombotic complications in the postoperative period worsens the course of the disease and increases mortality of children operated for congenital heart diseases (CDC). There is limited data on clinical risk factors of thrombosis after CDCs surgical correction in modern literature. In our opinion, there are several promising factors that have not been studied as predictors of thrombosis in children with CDCs. Aim of the study is to analyze possible effect of patient clinical characteristics on development of thrombotic complications in infants after surgical treatment of CDC. Methods. We have studied data of 156 children aged from birth to 11 months 29 days (median age - 5 months) with CDCs operated under artificial circulation. Following indexes were studied in all patients: age, surgical risk according to RACHS-1 (Risk adjustment for congenital heart surgery), anesthesia duration, surgery duration, aortic cross-clamping time, artificial circulation duration, gestation period, body weight and height at the time of surgery. Results. Thrombosis was diagnosed in 44 patients (28.2%) in the postoperative period. Thromboses of various localizations were found during the patients' examination: cerebral, intracardiac, limbs vessels, etc. It was revealed that thrombosis detection in patients with RACHS-1 >3 has increased in 2.84 times (95% CI: 1.36-5.92), at anesthesia duration >220 minutes - in 2.64 times (95% CI: 1.15-6.05), at surgery duration >150 minutes - in 3.36 times (95% MD: 1.51-7.5), at aortic cross-clamping time >32 minutes - in 3.23 times (95% CI: 1.45-7.32), at artificial circulation duration >70 minutes - in 3.43 times (95% MD: 1.6-7.34), with gestation period less than 39 weeks - in 2.44 times (95% CI: 1.18-5.03), with child's weight less than 5.000 grams - in 4.3 times (95% CI: 2.02-9.15), with child's height less than 60 centimeters - in 4.57 times (95% CI: 2.15-9.73), and at the age less than 3 months old - in 2.31 times (95% CI: 1.08-4.92). Conclusion. RACHS-1 >3, anesthesia duration >220 minutes, surgery duration >150 minutes, aortic cross-clamping time >32 minutes, artificial circulation duration >70 minutes, gestation period less than 39 weeks, weight at the time of surgery less than 5000 grams, height at the time of surgery less than 60 centimeters, and age under 3 months increases the risk of thrombotic complications in postoperative period.